Senior nurses’ perceptions of essential soft skills for novice nurses in a private hospital in Jakarta, Indonesia: A phenomenological study - Ernawati, Ernawati; Bratajaya, Cicilia Nony Ayuningsih (Belitung Raya Foundation, Indonesia, 2021)
Background: Nursing jobs are very complex and stressful, and nurses are demanded to have high competency and soft skills to keep their performance. However, the nursing workload often leads to fatigue, and it will be very challenging for novice nurses. Therefore, they need to be trained in soft skills in order to be able to control their emotion and adapt to the situation. Unfortunately, studies on essential soft skills for novice nurses in Indonesia are scarce; further research on this topic is a necessity. Objective: This study aimed to explore the perception of senior nurses about the essential soft skills for novice nurses during their work adaptation process. Methods: This qualitative study used an interpretive phenomenology approach, which was conducted in a private hospital in Jakarta, the capital city of Indonesia. Data were collected using semi-structured interviews from ten senior nurses selected using a purposive sampling technique. Data were analyzed using Gadamer’s hermeneutic approach. Results: Nine essential soft skills were developed for novice nurses during their transition phase from education to practice, including self-control, initiative, caring, self-motivated, hospitality, flexibility, adaptability, analytical skill, and presentation skill. Conclusion: Findings of this study serve as a basis for developing the soft skills of novice nurses in their clinical practice in hospitals in Indonesia. It is also recommended that soft skills should be included in the nursing education curriculum. However, soft skills are essential for novice nurses to succeed in their adaptation and future career.